Differential Progression of Motor Dysfunction Between Male and Female Fragile X Premutation Carriers Reveals Novel Aspects of Sex-Specific Neural Involvement - Loesch, Danuta Z.; Tassone, Flora; Atkinson, Anna; Stimpson, Paige; Trost, Nicholas; Pountney, Dean L.; Storey, Elsdon (Frontiers in Molecular Biosciences, 2021)
Expansions of the CGG repeat in the non-coding segment of the FMR1 X-linked gene are associated with a variety of phenotypic changes. Large expansions (>200 repeats), which cause the Fragile X Syndrome (FXS), are transmitted from the mothers carrying smaller expansions (55-200 repeats), termed premutation. Amongst a wide range of clinical problems, 8-16% of female carriers may experience the severe, late onset neurodegenerative condition: ‘Fragile X-Associated Tremor Ataxia Syndrome’ (FXTAS). Male premutation carriers have a 40-50% risk of developing FXTAS. Although this disorder is more prevalent and severe in male than female carriers, specific sex differences in clinical manifestations and progress of the FXTAS spectrum have been poorly documented. Here we compare the pattern and rate of progression in three motor scales: tremor/ataxia (ICARS), tremor (CRST), and parkinsonism (UPDRS), and in several cognitive and psychiatric features, between thirteen female and nine male carriers initially having at least one of the motor scores ≥10. Moreover, we document the differences in each of the above measures between the cross-sectional samples of 22 female and 24 male PM carriers of comparable ages with FXTAS spectrum disorder (FSD) who manifest one or more features of FXTAS. The results showed that progression was more than twice the rate in male than in female carriers -for the ICARS, twice as high in males on the CRST scale, but sex difference was negligible for the UPDRS. The overall psychiatric pathology score (SCL-90), and Anxiety and Obsessive/Compulsive domain scores showed a significant increase only in the female sample. These results were consistent with the pattern of sex differences between larger, cross sectional FSD samples, and with sex-specific distribution of MRI T2 white matter hyperintensities: all males, but no females, showed middle cerebellar peduncle white matter hyperintensities (MCP sign). In conclusion, the magnitude and specific pattern of sex differences in manifestations and progression of clinically recorded changes in motor performance and MRI lesion distribution support the notion of the existence of certain sex-limited factor(s) which, beyond the predictable effect of the second, normal FMR1 alleles in female premutation carriers, may have neuroprotective effects specifically concerning the cerebellar circuitry.